Philosophy and the cultural crisis. An approach based on Cornelius Castoriadis' work (2017)
This essay aims to pay tribute to the Greek philosopher and psychoanalyst Cornelius Castoriadis in the 20 years of his death and is a way of reintroducing their political and cultural thought in the Colombian academy because, despite his greatness has been little worked in the universities in Colombia. With this essay titled Philosophy and cultural crisis, I intend to register the thought of Castoriadis in the “classical tradition” of philosophy, seeing their work and ideas with original and profound categories elucidating “being” and thought with all the rigor the authors-philosophers who have dared to think about everything. I think the philosophy of Castoriadis from their categories mothers (magmas, radical imagination, instituting social imaginary, the historical-social, logic ensidic, instituted-institutive-circle primary creation) respond to this demand-emergency lucidly Greek teacher and artist of the athenian polis.